THE IMPACT OF BORDERLESS AREA ON THE POLICE INTERNATIONAL COOPERATION - Krutova, Ērika (Border Security and Management, 2016)
In 2007 after signing the Treaty of Lisbon cooperation among police and other competent law enforcement offices became the official European policy, although the denial of inner borders started already in 1985. Since that time it is radically changed the legal basis of police cooperation.In spite of the fact that the denial of inner borders has started police cooperation, now due to terroristic acts taking place directly in European Union discussions on resumption of borders happen more often. The aim of this article is to start the discussion why interstate police cooperation is still ineffective. The task of this article is to pay the attention to those normative and legal acts in different levels makes cross-border cooperation difficult, not simple and easy. A legal act comes into force but there is no a competent official who is ready to apply it. Thus the fulfilment of all formal demands takes place while the practical realisation lags far behind. While the European Union develops secure, free and legal environment widens several criminal authority powers, it still does not work on gaining the expected result. There is a small number of articles and publications on law offices cooperation tools as it is a very specific field. The author comes to the conclusion that without examining new tools there is no possibility to apply them correctly and effectively. Police departments’ different understanding and law enforcement offices’ traditional work methods embarrass the application of new and effective cooperation tools.